2022
DOI: 10.1021/acs.joc.2c00661
|View full text |Cite
|
Sign up to set email alerts
|

Reversible, Red-Shifted Photoisomerization in Protonated Azobenzenes

Abstract: Azobenzenes are among the best-studied molecular photoswitches and play a key role in the search for red-shifted photoresponsive materials for extended applications. Currently, most approaches deal with aromatic substitution patterns to achieve visible light application, on occasion paired with protonation to yield red-shifted absorption of the azonium species. Appropriate substitution patterns are essential to stabilize the latter approach, as conventional acids are known to induce a fast Z … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 49 publications
0
16
0
Order By: Relevance
“…Another limitation is that we have not considered azobenzene protonation and azo-hydrazone tautomerism. These effects can be facilitated by substituents such as NH 2 and OH, and by solvation in a protic solvent, weakening the NN double bond and lowering the isomerization barrier. Protonation from the solvent is not accounted for in a PCM description. Incorporating automated protonation tools into our workflow would be of interest in the future.…”
Section: Discussionmentioning
confidence: 99%
“…Another limitation is that we have not considered azobenzene protonation and azo-hydrazone tautomerism. These effects can be facilitated by substituents such as NH 2 and OH, and by solvation in a protic solvent, weakening the NN double bond and lowering the isomerization barrier. Protonation from the solvent is not accounted for in a PCM description. Incorporating automated protonation tools into our workflow would be of interest in the future.…”
Section: Discussionmentioning
confidence: 99%
“…The cis azo conformation of these compounds exhibits a π → π* transition that is not red-shifted ( i.e. , there are two absorption peaks, π → π* at ∼370 nm with ε ∼ 28,000 M –1 cm –1 and n → π* at ∼460 nm with ε ∼ 5000 M –1 cm –1 ). , There is no literature indicating that supramolecular stabilization of an azobenzene dye as a cis azo conformer can induce a large bathochromic and hyperchromic shift in azobenzene absorption . Thus, the only way that a protonated 4-amino- or 4,4′-diaminoazobenzene can exhibit an intense absorption band with peak maximum >500 nm and ε > 40,000 M –1 cm –1 is by forming an azonium tautomer. , Therefore, we infer that the complexation-induced absorption peak at 554 nm is due to CB7 capture and stabilization of mono- or bisprotonated 4,4′-diaminoazobenzene as an azonium tautomer in a trans azo conformation, and the likely structures of these alternative supramolecular complexes are illustrated in Figure .…”
Section: Resultsmentioning
confidence: 99%
“…35 Kortekaas and coworkers found that protonation of para -methoxyazobenzene resulted in a redshifted absorption spectrum. 34 The unprotonated dye isomerized to the cis -isomer under UV illumination. While small yields of protonated cis p -methoxyazobenzene was observed upon protonation with strong acids, protonation of the azo bond with weaker acids reduced the extent of observable photoisomerization.…”
Section: Introductionmentioning
confidence: 99%